Populismus und Extremismus in Europa: gesellschaftswissenschaftliche und sozialpsychologische Perspektiven - Brömmel, Winfried; König, Helmut; Sicking, Manfred (Europäische Horizonte, 2017)
Populist protest movements, groups and parties keep growing - they fuel feelings of resentment against Europe that feed on a general discomfort about politics, the government and the media. The contributions in this volume illuminate the murky terrain of nationalism, populism and extremism in Europe and ask for the reasons of the ever-increasing allure of anti-democratic fundamentalism, terrorism and environments of violence. In addition, they discuss how we can grasp the rationale of this resentment and the fascination with violence and fanaticism.